Meaning in life and its relationships with intrinsic religiosity, deliberate rumination, and emotional regulation. Issue 4 (October 2016) - Park, Chan Jeong; Yoo, Sung‐Kyung
Abstract : Meaning in life is one of the core elements of well‐being. Although meaning in life has received considerable research interest over the years, much of this research did not differentiate between the two categories of meaning, that is, search for meaning and meaning in life. The present study first investigated collective explanatory powers that intrinsic religiosity, deliberate rumination, and emotional regulation – three predictors selected based on past literature – have on these two types of meaning. In addition, mediational effects of deliberate rumination and emotional regulation in the links between intrinsic religiosity and search for meaning and presence of meaning were investigated. The participants were 326 undergraduate students in Seoul, South Korea. The hierarchical regression analyses found that while intrinsic religiosity contributed significantly in explaining only presence of meaning, deliberate rumination and emotional regulation had significant contributions in explaining both search for meaning and presence of meaning. Also, double mediational analysis using structural equation modelling revealed that deliberate rumination, but not emotional regulation, mediated the relationship between intrinsic religiosity and meaning in life. The implications and directions for future studies are also discussed.